(untitled) (Vietnam Journal of Community Medicine, 2026)
Preimplantation genetic testing for aneuploidy (PGT-A) has been increasingly widely used in assisted reproductive technology, particularly in patients with a history of recurrent pregnancy loss or repeated implantation failure. The development of next-generation sequencing (NGS) technology has increased the detection rate of mosaic embryos, posing many challenges in embryo transfer decision-making and subsequent pregnancy management [1–4]. Although many studies and case reports have demonstrated the possibility of achieving a healthy live birth after mosaic embryo transfer, the risks of persistent fetal mosaicism, confined placental mosaicism, and discordance among preimplantation genetic testing, prenatal diagnosis, and postnatal testing remain not fully clarified [2,5,6]. Therefore, case reports with comprehensive pre- and postnatal follow-up play an important role in providing real-world evidence for clinical practice. We report the case of a 32-year-old woman with infertility due to bilateral tubal obstruction and a history of recurrent pregnancy loss. Following one in vitro fertilization cycle combined with PGT-A, no euploid embryos were identified; only one complex mosaic embryo was available. After comprehensive genetic counseling, the patient elected to proceed with mosaic embryo transfer. Pregnancy was achieved after frozen–thawed embryo transfer. Prenatal diagnosis by amniocentesis confirmed mosaic trisomy 7 (20%). Serial fetal morphological assessments revealed no structural abnormalities. The infant was delivered preterm at 34 weeks and 5 days of gestation, with a birth weight appropriate for gestational age, and postnatal peripheral blood karyotype analysis showed no chromosomal abnormalities.